Penerapan Jurnalisme Warga Di Media Sosial Instagram Kabar Tebet - Suradi Suradi; Sisca T. Gurning; Melitina Tecoalu; Teguh Setiawan (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The development of telecommunications technology is increasingly opening up great opportunities for everyone to have their own media. So that opens up opportunities for everyone to become a citizen journalist. This research arises from the results of the increasingly widespread phenomenon of citizen journalists using social media such as Instagram to convey local news, such as at the sub-district or residential area level. The purpose of this research is to observe how citizen journalists apply journalism to convey news and information to citizens via Instagram. The research method uses a qualitative approach, literature, interviews, and analyzes content created by citizen journalists for one year. The results of the research show that the types of local news at the sub-district level with news values of proximity are really needed or in demand by residents of the area where the journalist lives.